A Review On SVC Control For Power System Stability With And Without Auxiliary Controller - Kamis, Zalina; Ab Ghani, Mohd Ruddin; Kamarudin, Muhammad Nizam; Mohd Shah, Hairol Nizam; Jano, Zanariah (Institute Of Advanced Engineering And Science (IAES), 2019)
Since the beginning of the last century, power system stability has been recognized as a vital problem in securing system operation. Power system instability has caused many major blackouts. This paper reviewed the previous technical works consisting of various methods of optimization in controlling power system stability. The techniques presented were compared to optimize the control variables for optimization of power system stability. Power system stability enhancement has been investigated widely in literature using different ways. This paper is focusing on SVC performance for enhancing power system stability either through SVC controlled itself or SVC controlled externally by other controllers. Static VAR compensators (SVCs) are used primarily in power system for voltage control as either an end in itself or a means of achieving other objectives, such as system stabilization. The analysis on performance of the previous work such as advantages and findings of a robust method approach in each technique was included in this paper.